The role of Samuel Taylor Coleridge in the world of lyrics - Farmanov Gayrat (Лучшие интеллектуальные исследования, 2024)
Abstract: The literary activity of Samuel Taylor Coleridge not only in poetry, but also in criticism and philosophy. As much as he was important for poetry as a poet, he was as important for poetry as a critic. His philosophy of poetry, formed over many years, had a profound impact on the field of literary criticism